2023
DOI: 10.25259/sni_312_2023
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms for predicting outcomes of traumatic brain injury: A systematic review and meta-analysis

Abstract: Background: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. The use of machine learning (ML) has emerged as a key advancement in TBI management. This study aimed to identify ML models with demonstrated effectiveness in predicting TBI outcomes. Methods: We conducted a systematic review in accordance with the Preferred Reporting Items for Systematic Review and Meta-Analysis statement. In total, 15 articles were identified using the search strategy. Patient demographics, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…One approach, with increasing interest in the literature, is a range of statistical approaches under the umbrella of Big Data Analytics [184] or Artificial Intelligence (AI) and machine learning [7,185,186]. There are a wide variety of mathematical models that can be utilized to try and identify occult relationships between variables using brute force statistical approaches from large aggregates of data.…”
Section: Issues With Integrating Protein Biomarkers In the Clinical D...mentioning
confidence: 99%
See 1 more Smart Citation
“…One approach, with increasing interest in the literature, is a range of statistical approaches under the umbrella of Big Data Analytics [184] or Artificial Intelligence (AI) and machine learning [7,185,186]. There are a wide variety of mathematical models that can be utilized to try and identify occult relationships between variables using brute force statistical approaches from large aggregates of data.…”
Section: Issues With Integrating Protein Biomarkers In the Clinical D...mentioning
confidence: 99%
“…These are tall orders, but all the necessary components are available: several potential mechanistic fluid-based protein biomarkers have already been identified [3]. Moreover, all the required technologies are readily available including analytical platforms enabling sensitive and multiplexed assays [4][5][6], as well as the necessary algorithms for data processing and machine learning (ML) [7]. However, to help to incorporate blood-based 2 of 22 protein biomarker data into a patient management tool, two critical dimensions of TBI need to be considered, the spectrum of disease severity and complexity and the time factor.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Severe TBI (sTBI) accounts for 8% of all TBI worldwide, with approximately 5.48 million people suffering from sTBI annually. 3 sTBI mortality is from 20% to 30% and its prognosis is mainly related to trauma severity. 3 Secondary brain injury following sTBI involves hemorrhagic and ischemic cerebral injury, and the specific pathophysiological mechanisms include inflammatory reaction, mitochondrial dysfunction, cortical spreading depression, oxidative stress, microvascular thrombosis, neuronal necrosis and apoptosis, brain edema and blood–brain barrier disruption.…”
Section: Introductionmentioning
confidence: 99%
“… 3 sTBI mortality is from 20% to 30% and its prognosis is mainly related to trauma severity. 3 Secondary brain injury following sTBI involves hemorrhagic and ischemic cerebral injury, and the specific pathophysiological mechanisms include inflammatory reaction, mitochondrial dysfunction, cortical spreading depression, oxidative stress, microvascular thrombosis, neuronal necrosis and apoptosis, brain edema and blood–brain barrier disruption. 4 Conventionally, the Glasgow coma scale (GCS) is selected as a clinical severity indicator, which can be used to discriminate the risk of poor clinical outcome of sTBI.…”
Section: Introductionmentioning
confidence: 99%
“…Courville E et al reported a systematic view and meta-analysis (2013–2020) demonstrating that much of this literature discusses in-hospital mortality and poor prognosis, but lacks a more specific focus on the ICU population to understand the predictive power of AIs in TBI patients [ 17 ]. In the last three years, there have been several reports on the prognosis and mortality risk of brain injury using ML techniques.…”
Section: Introductionmentioning
confidence: 99%